Succession of Fungal Communities at Different Developmental Stages of Cabernet Sauvignon Grapes From an Organic Vineyard in Xinjiang - Zhu, Lihua; Li, Tian; Xu, Xiaoyu; Shi, Xuewei; Wang, Bin (Frontiers in Microbiology, 2021)
Fungi present on grape surface considerably impact grape growth and quality. However, information of the fungal community structures and dynamics on the worldwide cash crop, the Cabernet Sauvignon grape, from the budding to ripening stages remains limited. Here, we investigated the succession of fungal communities on Cabernet Sauvignon grapes from an organic vineyard in Xinjiang, China at different developmental stages via high-throughput sequencing combined with multivariate data analysis. In total, 439 fungal amplicon sequence variants (ASVs) from six phyla were identified. The fungal communities differed over the budding to the berry stages. Moreover, Aspergillus, Malassezia, Metschnikowia, and Udeniomyces were predominant during the unripe stage, whereas Erysiphe, Cryptococcus, Vishniacozyma, and Cladosporium were dominant in the ripe stages. Notably, Vishniacozyma was the most abundant genus, conserved in all development stages. Moreover, network analysis resulted in 171 edges—96 negative and 75 positive. Moreover, fungal genera such as Vishniacozyma, Sporobolomyces, Aspergillus, Alternaria, Erysiphe, Toxicodendron, and Metschnikowia were present in the hubs serving as the main connecting nodes. Extensive mutualistic interactions potentially occur among the fungi on the grape surface. In conclusion, the current study expounded the characteristics of the Cabernet Sauvignon grape fungal community during the plant growth process, and the results provided essential insights into the potential impacts of fungal communities on grape growth and health.